Modele aproksymacyjne i zarządzanie adaptacyjne w ekonomii - Rutkowski, Romuald (Approximate Models and the Adaptave Management in the Economy, 2006)
This article refers the problem of the control some economic processes. The use techniques connected with the description of the dynamic system by using differential equations are proposed. The problem of estimation such models described by means of ordinary first-order differential equation is illustrated by an example.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1140, s. 23-32